PENYULUHAN KEWIRAUSAHAANA BAGI KARANG TARUNA DI DESA PAPAHAN, KECAMATAN TASIKMADU, KABUPATEN KARANGANYAR - Suprayitno, Suprayitno; Widajanti, Erni (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
This extension activity was conducted for Karang Taruna Desa Papahan, Kec. Tasikmadu, Kab. Karanganyar. The outcomes of this activity are: cheap participants' knowledge of the concept of entrepreneurship so that they have the right knowledge; benefit participants' insights on how to start a business and choose the right type of business; benefit participants' insights about possible business failures and ways to enter and resolve business failures.This activity is carried out with the following stages: Selection of participants to the community service, namely the board and members of Karang Taruna; Submission of lecture materials, with a view to fostering an entrepreneurial spirit; Implementation of evaluation Evaluation is done by: before counseling conducted a question-answer to know each participant's initial knowledge about entrepreneurship special techniques or how to start a business. After the counseling finished the question and answer again about the same material. By comparing the results of answers that have been done, it will be known whether there is an increase in knowledge about the entrepreneurship and scope.Keywords: Counseling, entrepreneurship, management